Aktivitas Antivirus Beberapa Ekstrak Tanaman terhadap Bean Common Mosaic Virus strain Black Eye Cowpea (BCMV-BIC) pada Kacang Panjang - Tri Asmira Damayanti; Martha Theresia Panjaitan (Universitas Lampung, 2014)
ABSTRACTAntivirus actitivity of several plant extracts against Bean common mosaic virus strain Black eye cowpea (BCMV-BlC) on Yard long bean. Bean common mosaic virus (BCMV) is an important virus on yard long bean and it is difficult to control. One of control effort way by utilizing antiviral substances of plant origin. The research was done to select and test the effectiveness of plant extracts in suppressing BCMV infection on yard long bean. Twenty two plant extracts were selected by (1) spraying the crude extract to Chenopodium amaranticolor leaves, then plant inoculated by BCMV 1 hour after spraying, and (2) mixturing the crude extract with sap containing BCMV, then inoculated mechanically to C. amaranticolor. Local necrotic lesion number and inhibition percentage are measured. All plant extract treatments were able to reduce Necrotic lokal lesion formation significantly compared to untreatment control. Further, fifteen plant extracts were selected to test their effectiveness in controlling BCMV on yard long bean in green house trial. The results showed that except geranium and red ginger treatment, other extract treatments were able to reduce significantly the disease incidence and severity, symptoms, and BCMV titer, respectively. Among tested extracts, Bougainvillea spectabilis, Mirabilis jalapa, and Celosia cristata are the most effective crude extracts in suppressing BCMV infection.